PEMANFAATAN LIMBAH PET SEBAGAI SUBSTITUSI AGREGAT HALUS PADA PAVING BLOCK - Reni Sulistyawati AM.; Pingit Broto Atmadi (Teodolita: Media Komunkasi Ilmiah di Bidang Teknik, 2020)
Garbage due to human activities is increasing because as the population increases, the level of publicconsumption is also getting higher. There is a need for environmental waste management with the maingoal of reducing waste and utilizing waste so that it is not truly useless and discarded. PolyethyleneTerephtalate (PET) is one of plastic type that can be easily recycled. Its use as an added ingredient ofpaving block is one of alternative to overcome the existing waste or plastic waste. The purpose of this research is to find out the average value of acceptable compressive strength andpercentage value of water absorption by paving blocks with fine aggregate substitution in the form ofpolyethylene terephtalate (PET) plastic counts for each composition. The comparison used for cementand sand is 1: 6. This study uses  the  SNI  03-0691-1996 method  about  Concrete  Brick  (paving block.  The  results  obtained  for  the  average compressive strength that can be received by paving blocks areas follows in normal paving block (0%) of 11.32 MPa, in paving blocks with an addition of 0.3% is12.31 MPa, in paving blocks with the addition of 0.4% is 12.70 MPa, in paving block with addition of0.5% is 14.55 MPa, and in paving blocks with an addition of 0.6% is 11.82 MPa. While for thepercentage value the absorption of paving block water obtained each of them as follows in normalpaving block (0%) is 10%, in paving blocks with addition of 0.3% is 8%, in paving blocks with anaddition of 0.4 % is 7%, on paving blocks with the addition of 0.5% is 5%, and on paving blocks with theaddition of 0.6% is 9% MPa.Key Words : Compressive Strength, Paving Block, Waste, Polyethylene Terephtalate (PET), Plastic,Water Absorption.ABSTRAKSampah akibat aktivitas manusia semakin banyak karena seiring bertambahnya jumlah penduduk,tingkat konsumsi masyarakat  juga  semakin  tinggi.  Perlu  adanya  pengelolaan  sampah  lingkungan dengan  tujuan  utama  untuk mengurangi sampah. Jenis Polyethylene Terephtalate (PET) merupakansalah satu jenis plastik yang dapat didaur ulang dengan mudah. Penggunaanya sebagai bahan tambahpaving block merupakan salah satu alternatif untuk menanggulangi limbah atau sampah plastik yangada. Tujuan dari penilitian ini adalah untuk me ngetahui nilai rata rata kuat tekan yang dapat diterima dannilai persentase penyerapan air oleh paving block dengan subtitusi agregat halus dalam bentuk cacahanplastik polyethylene terephtalate (PET) untuk tiap komposisi. Perbandingan yang digunakan untuksemen dan pasir yaitu 1 : 6. Penelitian ini menggunakan metode SNI 03-0691-1996 tentang Bata Beton (paving block). Hasil uji menunjukkan bahwa rata rata kuat tekan yang dapat diterima oleh paving block tiap komposisiadalah sebagai berikut, pada paving block normal (0%) sebesar 11,32 MPa, pada paving block denganpenambahan 0,3% sebesar 12,31 MPa, pada paving block dengan penambahan 0,4% sebesar 12,70 MPa,pada paving block dengan penambahan 0,5% sebesar 14,55 MPa, dan pada paving block denganpenambahan 0,6% sebesar 11,82 MPa. Sedangkan untuk nilai persentase penyerapan air paving blockyang didapat masing-masing adalah sebagai berikut, pada paving block normal (0%) sebesar 10%, padapaving block dengan penambahan 0,3% sebesar 8%, pada paving block dengan penambahan 0,4%sebesar 7%, pada paving block dengan penambahan 0,5% sebesar 5%, dan pada paving block denganpenambahan 0,6% sebesar 9% MPa.Kata kunci: Kuat Tekan, Paving Block, Sampah, Plastik, PET, Serap Air.